From Management to Engagement. Tour Guides in Skaftafell at Vatnajökull National Park - Schaller, Harald Josef, 1979- (2016)
Nature-based tourism is a major industry in Iceland and many protected areas are popular tourist destinations. The growth of tourism is accompanied by increased complexity and uncertainty. This makes decision-making for sustainable tourism development difficult, especially in protected areas. Their management is a complex endeavour which requires specialized knowledge to formulate sustainable management solutions. In this context, tour guides not only play an important role in the experience of visitors but also in helping to ensure that tourism is socially and environmentally responsible. Their experience can not only help in providing a safe and engaging tour experience within the natural environment, but also in protecting nature. This thesis aims to increase the understanding of the role of tour guides in protected area management in general, and explore whether their experience and knowledge can contribute for the management of Vatnajökull National Park in particular. The research project examines this from the perspective of four aspects: the self, the human environment, the perception of nature and changes thereof, and the state of protected area management. Semi-structured interviews and mental mapping with guides working at Skaftafell were used to analyse how guides perceive their role in the tourism sector and to elicit their opinions about the state of hiking trails in the area. The findings suggest that guides do indeed care for the natural and human environment in which they are working. In their opinion, they have valuable knowledge to help shaping protected area management in order to increase the safety of visitors and ensure that conservation targets are reached. They agree that the current business practices and public management procedures are not in a state that contributes to sustainable tourism. Guides argue for the inclusion of their specific knowledge in the decision-making process of protected areas. It is argued in the thesis that the compassion that guides express is a valuable ...